2010
DOI: 10.1007/s10753-010-9232-1
|View full text |Cite
|
Sign up to set email alerts
|

Expressions of Interleukin-1β and Interleukin-6 Within Aortas and Uteri of Rats with Various Severities of Ligature-Induced Periodontitis

Abstract: To investigate the associations of periodontitis with histological lesions in some other organs, various severities of periodontitis were induced in rats by 3/0 silk ligatures tied around different numbers of their molar necks. Six weeks after the initial placement of ligatures, all rats were sacrificed by an anaesthetic overdose. The distances from the cemento-enamel junction to the alveolar bone crest within the placement zone of the ligature and their contralateral zone in groups L(2) and L(3) were measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 50 publications
2
6
0
Order By: Relevance
“…Ma et al reported that ligature increased the serum IL-6 levels but not those of IL-1β. consistent with our findings [ 42 ]. This suggests that the serum cytokine levels in ligature-induced PD is not reflected in periodontal tissue inflammation.…”
Section: Discussionsupporting
confidence: 94%
“…Ma et al reported that ligature increased the serum IL-6 levels but not those of IL-1β. consistent with our findings [ 42 ]. This suggests that the serum cytokine levels in ligature-induced PD is not reflected in periodontal tissue inflammation.…”
Section: Discussionsupporting
confidence: 94%
“…the systemic vasculature, as this bacteria has been found in atheroma plaques (Haraszthy et al, 2000) and thrombi from patients with acute myocardial infarction (Ohki et al, 2012). In addition, and strengthening the validity of the animal model used in this study, increased nitration of cardiac proteins (Ma, Guo, You, Xia, & Yan, 2011) and enhanced lipid deposits in aorta (Bain et al, 2009) have been detected in rats seven days after ligature induced-periodontitis.…”
Section: Discussionsupporting
confidence: 70%
“…In addition, accelerated atherosclerosis progress has been found in apoE −/− mice by oral or intravenous inoculation of P. gingivalis or Fusobacterium nulceatum (Lalla et al 2003 ; Li et al 2002 ; Velsko et al 2015 ). Furthermore, a ligature-induced periodontitis rat model, increased lipid peroxidation and IL-6 expression was observed in aortic wall (Ma et al 2010 ). In the present study, decreased periodontal destruction after NSPT was observed, therefore, less periodontal pathogens and their byproducts was released into the blood stream, leading to less inflammatory response in the arterial wall.…”
Section: Discussionmentioning
confidence: 99%